Glyphosate and aminomethylphosphonic acid removal by fungal strains native to pesticide-exposed agricultural soil: a field study - Carranza, Cecilia Soledad (2024)
Several studies, have reported that glyphosate-based herbicides persist in the soil and are transported into other environmental matrices. This study evaluated the ability of Aspergillus oryzae AM2 and Mucor circinelloides 166 to remove glyphosate and aminomethylphosphonic acid from agricultural soil under field conditions. The strains are native to Argentinean agricultural soils, and they were assessed separately and in combination in 2 m × 1 m subplots. A completely randomized block design was used (5 treatments with 6 replicates each). The soil was sprayed with a commercial glyphosate-based herbicide formulation (3 kg ha-1) and inoculated with spores and/or conidial suspensions. Glyphosate and aminomethylphosphonic acid were measured at the beginning of the assay and at the end (150 days) by ultra-high performance liquid chromatography. In all the treatments, residual glyphosate levels were significantly lower at the end than at the start. The most significant removal percentages (p < 0.001) were 97%, obtained with A. oryzae AM2 (10exp6 conidia/mL-1), and 93%, obtained with the combination of M. circinelloides 166 (10exp6 spores mL-1) and A. oryzae AM2 (10 exp3 conidia mL-1). Aminomethylphosphonic acid decreased significantly (by 32%) in the uninoculated control. The same two treatments that were the most effective at removing glyphosate were the only ones in which the decrease in aminomethylphosphonic acid was higher than in the control (over 70%). This is the first study to demonstrate that these fungal strains can remove glyphosate and aminomethylphosphonic acid under field conditions. Thus, they could be good candidates for the remediation of herbicide-polluted sites.